The role of the National Archives and Records Service of South Africa in the young democracy - Masimba, Yuba (My University, 2014)
The NARS is the body charged with the proper management and care of the records of all public bodies in the South African public sector. it has been facing steep challenges in pursuing this mandate. Factors such as a shortage of staff, lack of space in the archival repository, and the inability to enforce compliance have rendered NARS incapable of performing its tasks. The premise of this research was based on the assumption that there is a neglect of NARS and record-keeping function in the public sector. The purpose of the research was to gather evidence of this claim and to understand the underlying reasons behind the neglect. A qualitative methodology was used to collect and analyse data using a field study design. The research revealed that NARS is unable to perform its duties in the public sector because its function is not recognised as vital to the pursuance of objectives in the public sector. Records are not valued due to the lack of priority of basic administrative activities, which has resulted in the neglect of records management. The study contends that the influence of the New Public Management (NPM), particularly the aspect of management which focuses on increasing the capacity of managers in order to enhance efficiency, has led to the lack of prioritisation of basic but important administrative activities, records management included.
Thesis (M.M. (Research))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Archives; Records; Management; Public records; South Africa